Blood expiation in Hittite and biblical ritual origins, context, and meaning - Feder, Yitzhaq; American Council of Learned Societies (Atlanta : Society of Biblical Literature, 2011)
This pioneering study examines the use of blood to purge the effects of sin and impurity in Hittite and biblical ritual. The idea that bloo d atones for sins holds a prominent place in both Jewish and Christian traditions. The author traces this notion back to its earliest document ation in the fourteenth- and thirteenth-century B.C.E. texts from Hitti te Anatolia, in which the smearing of blood is used as a means of expia tion, purification, and consecration. This rite parallels, in both its procedure and goals, the biblical sin offering. The author argues that this practice stems from a common tradition manifested in both cultures . In addition, this book aims to decipher and elucidate the symbolism o f the practice of blood smearing by seeking to identify the sociocultur al context in which the expiatory significance of blood originated. Thu s, it is essential reading for anyone interested in the meaning and eff icacy of ritual, the origins of Jewish and Christian notions of sin and atonement, and the origin of the biblical blood rite.
Part 1 ; 1: The Hurro-Hittite zurki Rite -- 2: The Biblical Sin Offe ring -- 3: The Question of a Historical Connection -- Part 2 ; 4: Ritua ls, Signs, and Meaning: Theoretical Foundations -- 5: The Blood of the Sin Offering: Origins, Context, and Meaning -- 6: The zurki Rite: Origi ns, Context, and Meaning -- 7: Tracking the Blood Rite Tradition: Origi ns, Translation, and Transformation -- Conclusion
Includes bibliographical references and indexes.
Electronic text and image data.
Keywords: Blood in the Bible; Blood -- Religious aspects; Ritual; Hittites -- Religion